The Effectiveness of Semantics Feature Analysis on EFL Primary Learners’ Word Awareness - Hussein, Riwan; Mohammed, Fakhir (Humanities Journal of University of Zakho, 2022)
The correlation between the thematic and lexical units is a fundamental stage in language development. Understanding vocabulary from any text and category is essential in school subjects and daily life. Therefore, the current study aims at examining and analyzing the effect of semantic feature analysis (henceforth, SFA) strategy on the word awareness of EFL primary learners. The present study participants are twenty-three learners with language delay (LD), who are learning English as a second language at Da Vinci International School and Smart Kurd Private School, Duhok city, Kurdistan Region of Iraq. Furthermore, to achieve the research aims, a qualitative methodology was used, whereby students were observed, and data was collected through two main tasks, a matrix chart with and without graphical representation. The results showed that students faced fewer difficulties when identifying the physical features of lexical items in both matrixes. By contrast, the participants tended to find location features as the most difficult category. The study has also revealed that SFA with graphic representation is greatly effective in terms of vocabulary learning and retention. Moreover, this study is valuable as it investigated the effectiveness of SFA on primary learners’ word awareness. It contributes largely to children's language development in terms of lexicon enrichment, comprehension, and content retention.